التدقيق الاجتماعي كأداة لحوكمة الموارد البشرية في المؤسسات الاستشفائية - زيان, يوسف; قارة تركي, آسيا (جامعة الوادي University of Eloued, 2021)
الهدف من هذه الدراسة هو إبراز دور التدقيق الاجتماعي في حوكمة الموارد البشرية في المؤسسات الاستشفائية ، حيث أنه يسعي إلى تقييم وتحليل قدرة المؤسسة على التحكم في مواردها البشرية باستعمال تقنيات تسمح بالكشف عن نقاط الضعف والقوة بهدف بلوغ حوكمة الموارد البشرية بفعالية . وقد توصلنا إلى نتيجة مفادها أن تطبيق التدقيق الاجتماعي في المؤسسات الاستشفائية يساهم في الاستغلال الأمثل لرأس المال البشري لا سيما عند إدارك الموظفيين لمبادئ التدقيق الاجتماعي وتطبيقهم لمبادئ حوكمة الموارد البشرية. The aim of this study is to highlight the role of social audit in human resources governance in hospital institutions, as it seeks to assess and analyze the ability of the institution to control its human resources using techniques that allow the detection of weaknesses and strengths in order to achieve human resources governance effectively. We have come to the conclusion that the application of social audit in hospital institutions contributes to the optimal exploitation of human capital, particularly when employees are introduced to the principles of social audit and their application of the principles of human resources governance
Social auditing as a tool for human resource governance in hospital institutions a case study of the University Hospital of Tlemcen
مقال
Keywords: التدقيق. الاجتماعي.، الموارد. البشرية.، المؤسسات. الاستشفائية.، الحوكمة.، المبادئ.